Generating and Financing Growth : Essays on Intangible Capital, Entrepreneurship, and Capital Structure in Finnish SMEs - Norkio, Antti (Vaasan yliopisto, 2024)
This doctoral dissertation contains three essays focusing on both the role of intangible capital (IC) and entrepreneurship in growth firms and the dynamics of their capital structure. IC is measured using an occupation-based method. The first essay considers how IC and an entrepreneur’s education are related to firm growth in small and medium-sized enterprises (SMEs). The results show that IC is an important factor for firm growth. In addition, an entrepreneur’s higher tertiary technical education has a positive relationship with firm growth. Instead, an entrepreneur’s higher tertiary business education is negatively related to growth. The other fields of education and higher education in general are unrelated to firm growth. The second essay examines how IC is related to financial leverage in SMEs. In addition, there are supplemental estimations in appendix that include entrepreneurs’ education as a regressor. The results show that IC has a negative relationship with financial leverage, likely caused by its weak pledgeability. This makes internal finance particularly important for intangible investments. The results also indicate that entrepreneurs possessing higher technical education operate with lower financial leverage than others, while higher tertiary business education is related to higher financial leverage. The third essay investigates how the capital structure develops when an SME generates high growth for the first time over a 3-year period. Propensity score matching with difference-in-differences (PSM-DID) is used to reveal the relationship between high growth and development of the capital structure. This approach enables us to match high-growth firms (HGFs) with control firms that have similar covariates. The results indicate that short-term debt is the most frequently used source of finance in high-growth SMEs. While control firms decrease their long-term financial leverage and increase their equity ratio, HGFs decrease both their long-term financial leverage and equity ratio. This highlights the importance of short-term credit access for high-growth SMEs. These findings emphasize the potential risk in the capital structure of high-growth SMEs during a tightening credit market if long-term assets are being financed by short-term debt.

Tämä väitöskirja koostuu kolmesta esseestä keskittyen aineettoman pääoman ja yrittäjien rooliin kasvuyrityksissä sekä niiden pääomarakenteen dynamiikkaan. Aineeton pääoma on laskettu käyttäen ammattiperusteista metodia. Ensimmäinen essee tutkii, kuinka aineeton pääoma ja yrittäjän koulutus ovat yhteydessä pienten ja keskisuurten yritysten kasvuun. Tulokset osoittavat, että aineeton pääoma on tärkeä tekijä kasvuyrityksissä. Lisäksi yrittäjän tekniikan alan ylempi korkeakoulutus on yhteydessä yrityksen kasvuun. Sen sijaan yrittäjän kaupallinen ylempi korkeakoulutus on negatiivisesti yhteydessä kasvuun. Muilla koulutusaloilla tai korkeakoulutuksella yleensä ei havaita olevan yhteyttä yrityksen kasvuun. Toinen essee tarkastelee, kuinka aineeton pääoma selittää pk-yritysten velkaisuutta. Lisäksi väitöskirjan liitteissä olevissa estimoinneissa yrittäjän koulutus on lisätty selittäjäksi. Tulokset osoittavat, että aineettomalla pääomalla on negatiivinen yhteys yrityksen velkaisuuteen, mikä todennäköisesti johtuu sen huonosta panttauskelpoisuudesta. Tulorahoitus on siksi erityisen tärkeää aineettomille investoinneille. Lisäksi liitteissä esitetyt tulokset indikoivat, että teknisen korkeakoulutuksen omaavat yrittäjät toimivat keskimäärin matalammalla velka-asteella kuin muut, kun taas kaupallinen ylempi korkeakoulutus on yhteydessä korkeampaan velka-asteeseen. Kolmas essee tutkii, kuinka pääomarakenne kehittyy, kun pk-yritys kasvaa ensimmäistä kertaa nopeasti kolmen vuoden ajan. Korkean kasvun ja pääomarakenteen kehityksen välinen suhde osoitetaan käyttämällä propensity score matching with difference-in-differences –metodia. Se mahdollistaa korkean kasvun yritysten vertaamisen samankaltaisiin kontrolliyrityksiin. Tulokset osoittavat, että lyhyen aikavälin laina on eniten käytetty rahoituslähde korkean kasvun pk-yrityksissä. Kun kontrolliyritykset vähentävät pitkän aikavälin velkaisuutta ja lisäävät omavaraisuusastetta, korkean kasvun yritykset vähentävät kumpaakin. Tämä korostaa lyhyen aikavälin lainan saatavuuden tärkeyttä korkean kasvun pk-yrityksille. Nämä löydökset alleviivaavat potentiaalisia riskejä korkean kasvun pk-yritysten pääomarakenteessa kiristyvien rahoitusmarkkinoiden aikana, mikäli pitkäaikaiset omaisuuserät on rahoitettu lyhyen aikavälin lainalla.
Keywords: enterprises; finance; growth; entrepreneurship; small and medium-sized enterprises; business operations; entrepreneurs; effects on employment; fi=Taloustiede|en=Economics|